ASUHAN KEPERAWATAN PADA PASIEN DENGAN DIABETES MELLITUS TIPE II DI KAMPUNG SASAK RAYA KELURAHAN LIMO, KOTA DEPOK JAWA BARAT - Apriani Dwi Susanti, (2023)
Background: Diabetes Mellitus (DM) is a disorder characterized by increased levels of glucose in the blood because the body cannot produce insulin effectively, because the function of insulin is to help the body control blood sugar levels and manage glucose as an energy source through fat. cells, muscle cells, and the heart. Diabetes Mellitus occurs due to several factors such as genetics, environment, wrong lifestyle, unhealthy eating patterns, obesity, age, which is characterized by nursing care for type 2 diabetes mellitus patient in Kampung Sasak Raya Limo Village Depok City West Java. If left untreated, diabetes mellitus can cause chronic complications and occur chronically. Purpose: This research can provide nursing care to Mrs. S with glucose instability in the blood in the area of Kampung Sasak Raya, Depok City. Method: This study uses the case study method in nursing care for clients Ny. S with unstable blood sugar levels in the Kampung Sasak Raya area of Depok City from 20 February to 23 February 2023. Data collection was carried out by means of interviews, observation or monitoring, and documentation.